Implementation of the Disaster Risk Mitigation Education Learning Model to Increase Family Preparedness for Flood Disasters in the Kemayoran Area - Saka Adhijaya Pendit; Meulu Primananda; Riza Ginanjar Mustofa (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
Flooding is a frequent disaster in urban areas, including Kemayoran, Jakarta, which has the potential to cause physical, economic, and health losses. Family preparedness is an important factor in efforts to reduce the impact of disasters. One strategy that can be implemented to improve family preparedness is through disaster risk mitigation education. This study is a study that uses a Quasi-Experimental research design, with a one-group pretest-posttest design method. This study was conducted by administering a pretest before being given an intervention, after which the intervention was given and finally a posttest was administered. Therefore, this type of research is included in the Quasi-experimental. The results showed that before the intervention, 36 respondents (60%) had a good category of preparedness and 24 respondents (40%) were in the moderate category. After the intervention, the number of respondents with a good category of preparedness increased to 42 respondents (70%), while the moderate category decreased to 18 respondents (30%). The Wilcoxon Signed Rank Test results showed a Z value of -2.336 with a p-value of 0.013 (p < 0.05), which means there is a significant difference between the level of family preparedness before and after the intervention. The application of the disaster risk mitigation education learning model has a significant effect on increasing family preparedness for flood disasters in the Kemayoran area. This learning model can be used as a family-based disaster education strategy to improve the community's ability to face the risk of flood disasters.